Well-known surface and extracellular antigens of pathogenic microorganisms among the immunodominant proteins of the infectious microalgae Prototheca zopfii - Irrgang, Alexandra; Murugaiyan, Jayaseelan; Weise, Christoph; Azab, Walid; Roesler, Uwe (Frontiers in Cellular and Infection Microbiology, 2015)
Microalgae of the genus Prototheca (P.) are associated with rare but severe infections (protothecosis) and represent a potential zoonotic risk. Genotype (GT) 2 of P. zopfii has been established as pathogenic agent for humans, dogs, and cattle, whereas GT1 is considered to be non-pathogenic. Since pathogenesis is poorly understood, the aim of this study was to determine immunogenic proteins and potential virulence factors of P. zopfii GT2. Therefore, 2D western blot analyses with sera and isolates of two dogs naturally infected with P. zopfii GT2 have been performed. Cross-reactivity was determined by including the type strains of P. zopfii GT2, P. zopfii GT1, and P. blaschkeae, a close relative of P. zopfii, which is known to cause subclinical forms of bovine mastitis. The sera showed a high strain-, genotype-, and species-cross-reactivity. A total of 198 immunogenic proteins have been analyzed via MALDI—TOF MS. The majority of the 86 identified proteins are intracellularly located (e.g., malate dehydrogenase, oxidoreductase, 3-dehydroquinate synthase) but some antigens and potential virulence factors, known from other pathogens, have been found (e.g., phosphomannomutase, triosephosphate isomerase). One genotype-specific antigen could be identified as heat shock protein 70 (Hsp70), a well-known antigen of eukaryotic pathogens with immunological importance when located extracellularly. Both sera were reactive to glyceraldehyde-3-phosphate-dehydrogenase of all investigated strains. This house-keeping enzyme is found to be located on the surface of several pathogens as virulence factor. Flow-cytometric analysis revealed its presence on the surface of P. blaschkeae.